The importance of the doctrine of justification in the theology of Thomas F. Torrance and of Karl Barth. Issue 2 (19th April 2017) - Molnar, Paul D.
Abstract: This discussion of the interaction between Thomas F. Torrance and Karl Barth first highlights how and why the doctrine of justification binds them together theologically, since each theologian applies this doctrine relentlessly to all aspects of theology. The article then explores how their views of religion illustrate their thinking. Finally, it considers two areas of disagreement between Barth and Torrance regarding the issue of subordination within the doctrine of the Trinity and the possibility of natural theology.